MXene‐Derived Ferroelectric Crystals - Tu, Shaobo; Ming, Fangwang; Zhang, Junwei; Zhang, Xixiang; Alshareef, Husam N. (Advanced materials (Weinheim), 2019)
This study demonstrates the first synthesis of MXene‐derived ferroelectric crystals. Specifically, high‐aspect‐ratio potassium niobate (KNbO3) ferroelectric crystals is successfully synthesized using 2D Nb2C, MXene, and potassium hydroxide (KOH) as the niobium and potassium source, respectively. Material analysis confirms that a KNbO3 orthorhombic phase with Amm2 symmetry is obtained. Additionally, ferroelectricity in KNbO3 is confirmed using standard ferroelectric, dielectric, and piezoresponse force microscopy measurements. The KNbO3 crystals exhibit a saturated polarization of ≈21 µC cm−2, a remnant polarization of ≈17 µC cm−2, and a coercive field of ≈50 kV cm−1. This discovery illustrates that the 2D nature of MXenes can be exploited to grow ferroelectric crystals. MXene‐derived high‐aspect‐ratio potassium niobate (KNbO3) single crystals are successfully synthesized using 2D Nb3C MXene and potassium hydroxide (KOH) as the niobium and potassium source, respectively. The well‐defined butterfly loops of the piezoresponse force microscopy amplitude signals and the distinct 180° switching of the phase signals further corroborate the presence of robust ferroelectricity in M‐KNbO3 crystals.